Intracardiac 3D navigation as a tool to improve the efficiency of ablation of idiopathic ventricular arrhythmias - S. Yu. Prorok; M. M. Dolzhenko (Сучасні медичні технології)
Aim. Еvaluate the effect of 3D navigation on the effectiveness of ablation idiopathic ventricular arrhythmias.